Influência do processo de moldagem e de cura nas propriedades do concreto de ultra alto desempenho - Carvalho, Carlos Maviael de (2019)
Ultra High-Performance Concrete (UHPC) also called Reactive Powder Concrete (RPC) represents an evolution in the field of application of Portland cement-based materials. In addition to the conventional materials used to obtain common concrete, RPCs require considerable amounts of very thin materials and high-efficiency additives to achieve compressive strengths exceeding 150 MPa. This type of concrete is a more expensive and more complex material for manufacturing, not yet having its use worldwide.Given its potential for making slim precast and even ceramic floor tiles, this research was proposed. Initial high strength cement, quartz powder or basalt powder, active silica and two types of additives were used. The packaging theory was used to reach the various fractions of the aggregate.After intense experimental program it was possible to work with water / agglomerate ratio of 0.20. Two concrete mixes were used, the only difference being the aggregate: quartz powder in mix 1 and basalt powder in mix 2. From each concrete mix was prepared in the four conditions: cure in laboratory environment (reference); bath at 80°C for one day, static pressure compaction; and autoclave cure.Fresh and hardened concrete characterization tests were performed to obtain consistency, compressive strength, flexural tensile strength, diametral compression tensile strength, immersion and capillary absorption, air permeability.The microstructure of the concretes was studied through differential thermal analysis. The results point to the feasibility of making the CPR locally and show that the best performance was obtained with the compression molding, reaching values of resistance to compression that reached 169 MPa. However, curing under environmental conditions has also produced a concrete of excellent properties.